Advancing water resources management in Honduras: Agua de Honduras Platform’s comprehensive impact and nationwide institutional adoption - Valencia, Jefferson (2024)
The Agua de Honduras Platform has delivered diverse and impactful outcomes, including water source identification for a new aqueduct for the resettled Yarushin community, adoption by organizations like World Vision and Helvetas, and legalization of watershed management councils. It supports community-led water planning, guides land conservation efforts, and aids in risk management. Additionally, it optimizes project approaches, ensuring resource-use efficiency and sustainable water access, while preventing ineffective infrastructure construction, as seen in El Aguacatillo (Lempira)